A novel method to produce few layers of graphene as support materials for platinum catalyst - Ozdemir, Oguz Kaan (SPRINGER INTERNATIONAL PUBLISHING AG, 2019)
There are two main obstacles preventing the commercialization of polymer electrolyte fuel cells (PEMFCs) such as low durability of support material and high cost of metal catalyst. It is necessary to use support materials to increase the distribution of the catalysts and to be accumulated more in the active area. Despite widespread usage of carbon as support material, carbon suffers from oxidation under fuel cell working conditions. In the past several years, researchers have given many efforts to develop new support materials, which have high surface area, and are electrically conducting and chemically stable. Among all support materials, graphene, thanks to two-dimensional graphite form, has unique physical and electrical properties; because of these superior features, graphene can be an ideal support material for nanoparticles. In this study, we updated the Hummers' method by addition of certain amount of potassium dichromate in addition to potassium permanganate as oxidant agent. After that, graphene oxide was uniformly coated with conductive polyaniline (PANI) polymers by the liquid-liquid interface polymerization method. Finally, PANI/GO composite was pyrolyzed at certain temperature and time to reduce graphene oxide to few layers of graphene. Electrochemical active surface area (EASA) of commercially obtained Pt/VulcanXC-72 was calculated as 29.5m(2)/gPt, while EASA of Pt/RGO catalysts was 63.7m(2)/gPt.
Keywords: Graphene oxide; Polyaniline; Reduced graphene oxide; Electrocatalyst; PEM fuel cell; ELECTROCATALYSTS; PERFORMANCE; REDUCTION; Chemistry